Անգլո-ռուսական մրցակցությունը և թուրք-պարսկական վերջին՝ 1821-1823 թթ. պատերազմը - Լ. Ա. Մկրտումյան (ՀՀ ԳԱԱ հրատ.)
В межгосударственных отношениях стран Ближнего и Среднего Востока в силу геополитических и экономических причин особое место занимают ирано-турецкие отношения. В XV-XVIII вв. эти отношения нашли отражение в перманентных войнах между этими двумя странами, стремившимися установить контроль над связывающими Европу с Востоком стратегически важными путями и занять доминирующее положение в исламском мире. Turkish-Iranian relations had been of a special importance among the countries of the Middle East due to a number of geopolitical and economic reasons. In the XV-XVIII centuries these relations were expressed in the permanent wars between this two countries aiming at the establishing control over strategically important routes connecting Europe with the East and taking a leading position in the Islamic world.
Keywords: History; Political Science; Modern History; D History; J Political Science